PERLINDUNGAN HUKUM TERHADAP KONSUMEN AIR ISI ULANG DI KECAMATAN JOHAN PAHLAWAN - Sari, Tri Ajar; Trisna, Nila; Jhowanda, Rahmat (Prodi Ilmu Hukum, Universitas Teuku Umar, 2024)
Article 4 of the Consumer Protection Law grants consumers the right to comfort, safety, and security when consuming goods and/or services. However, in practice, there are 32 refillable water depots in the Johan Pahlawan District that operate without permits. This indicates a violation of the Consumer Protection Law regulations. The purpose of this research is to understand the legal provisions for consumers related to refillable water depots in the Johan Pahlawan District and to identify the obstacles in implementing the Consumer Protection Law. The research method used is empirical juridical. The implementation of legal protection in the Johan Pahlawan District has not been effective due to consumers still not receiving their rights regarding refillable water quality standards, and they continue to feel disadvantaged due to irresponsible business operators. The main obstacles faced by refillable water depots in the Johan Pahlawan District in implementing Law Number 8 of 1999 concerning Consumer Protection are related to both business operators and consumers lacking legal knowledge about the Consumer Protection Law.